The Link between Corporate Social Responsibility (CSR), Innovation and Competitive Advantage – An Exploratory Study - Durrani, Muhammad Faheem (2008)
Governments and activists alike are increasingly holding companies to account for the social repercussions of their actions. As a consequence, corporate social responsibility (CSR) has become an inescapable priority for business readers worldwide. However, the new millennium gave rise to a new paradigm in the field of CSR. Executives, caught between the conflicting demands of shareholders demanding higher profits and other stakeholders demanding more accountability, have adopted a more strategic approach towards CSR. They view the expectations and needs of the community as an opportunity to develop novel business solutions (innovation) and demonstrate superior business technology that allows to them gain a competitive advantage over their rivals. The aim of this dissertation is to contribute to this new model of CSR. The dissertation seeks to explore this new paradigm of CSR with an eye towards understanding the various dimensions of the link between CSR, innovation and competitive advantage. The dimensions studied here include ‘CSR Aspect’, ‘Theoretical Perspective’, ‘Innovation Type’ and ‘Outcome’. This dissertation will hopefully provide useful insights into the process of encompassing CSR into core business strategy, describing such behavior along dimensions that will be useful for executives who wish to adopt this new model. To achieve the above objectives, an exploratory study of nine firms from various industries was carried out. The firms that were chosen all had CSR programs that were part of their business strategies, allowing for the research questions to be tested on their behavior. Data for this study was collected from a triangulation of secondary sources, namely corporate websites, annual reports, standalone CSR reports, books and a variety of published material such as journals and magazines. A content analysis was then used as the analytical tool to analyze the collected data to reveal any similarities and patterns that might emerge from the data. Results indicate that such a strategic outlook towards CSR did prove to be a source of innovation for the firms, the outcome being a competitive advantage in each case. What’s more, out of the four dimensions studied, theoretical perspective and innovation type were the only ones with an identifiable link between them. These findings provide implications for managers and policy makers alike. Managers that do not pit business against society, and align company strategy with its CSR find out that the social sector can be an effective source of innovation and competitive advantage. Governments need to have the right policies and incentives in place find shared value in firms operations and in the social dimensions of competitive context. They need to shift their mindset from one of corporate social responsibility to corporate social integration.